Oscillating supersonic delta wings with curved leading edges - Khan, Sher Afghan; Crasta , Asha (The Jangjeon Mathematical Society (JMS), 2010)
In the present study Supersonic similitude has been used to obtain stability derivatives in pitch and roll of a delta wing for the attached shock case. A strip theory is used in which strips at different span-wise locations are independent. This combines with the similitude to give a piston theory. The present theory is valid only for attached shock case. Effects of wave re ection and viscosity have not been taken into account. Some of the results have been compared with those of Hui et al (1982), Ghosh (1984), and Liu and Hui (1977). Results have been obtained for supersonic ow of perfect gas over a wide range of Mach numbers, incidences and sweep angles. A good agreement is obtained with Hui et al in some special cases.